Refugee response in Egypt: A public administration and policy perspective. A case study of Syrian refugee response in Egypt: 2012 to the present - Elshokeiry, Nadine (AUC Knowledge Fountain, 2016)
This descriptive and exploratory study attempts to look at refugee response in Egypt. It takes the Syrian refugee response in Egypt as a holistic single-case study to understand what the Egyptian government did, and why. The study aims to discuss the case study and its surrounding context from an overarching public policy and administration perspective, through a Public Policy System approach coupled with Jacobsen’s Theory of Public Policy Choices in Host states. It proceeds from a right-based approach to refugees issues, and employs a number of methodologies to provide a full perspective of the topic of study, including a comparative historical analysis and a legal analysis. The study concludes with a number of findings on Egypt’s role in the Syrian refugee responses and its general policy and administration approach on the issues, and puts forth a number of recommendations to guide future response management in Egypt.